RAD-Based Public Opinion Monitoring Information System for BSN - Arianty, Kiki Puspo (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
The growing influence of online media in shaping public opinion has driven government institutions to modernize their monitoring and communication systems. This study aims to develop a web-based information system for monitoring public opinion, tailored to the needs of the National Standardization Agency of Indonesia (BSN). Using the Rapid Application Development (RAD) approach, the system was built through a phased prototyping and user involvement to ensure functional relevance. The final system enables sentiment classification of news articles, centralized data storage, trend visualization, and automated news clipping. Evaluation results indicate improvements in monitoring speed, accuracy, and usability compared to previous manual methods. This study confirms the effectiveness of RAD in building practical digital tools for public sector communication and reputation management.